The market in the theory of regulation - Campbell, David (2018)
This article reviews developments in the left-wing theory of regulation in response to the neo-liberal revolution of the 1970s. The core of this response has been an acknowledgement of the indispensability of market ordering, but this acknowledgement has been only grudging and no positive theory of the market has emerged from regulatory proposals which concentrate on market failure. A sort of inchoate communism therefore pervades the left-wing theory of regulation, and left-wing regulatory theory and practice still lacks a coherent concept of market socialism. - Reproduced.
Keywords: Market - Regulation; Socialism